Visual Interactivity: Communication Strategy for Labuan Bajo Cultural Tourism Branding - Julianto, I Nyoman Larry; Lestawi, I Nengah; Yasa, I Ketut Wardana; Hasbullah, Hasbullah (Universitas Ciputra, 2026)
The development of digital technology has prompted the global community to turn to more interactive and accessible media to simulate future experiences. In the context of tourism, digital media is a strategic means in building the image of destinations, including in strengthening Labuan Bajo's tourism branding as a leading cultural tourism destination. However, there are still issues related to effective branding communication strategies in creating interactivity and immersive experiences for potential travelers. Research that raises the integration of local culture as the main content in interactive media to support sustainable tourism branding has also not been explored in depth. Most studies have not examined how the values of local wisdom can be packaged immersively and strategically to create destination differentiation. This study aims to analyze the branding communication strategy of Labuan Bajo cultural tourism destinations that are able to increase attractiveness through an interactive approach. The method used is descriptive qualitative with data collection techniques in the form of interviews with Mr. Hatta and Mr. Evan and literature studies. Data analysis was carried out using the theoretical approach of Aristotle's Rhetoric which emphasizes aspects of ethos, pathos, and logos in message delivery. The results of the study show that the integration of Labuan Bajo's local cultural elements into interactive Virtual Reality 360° media is able to create a more immersive branding communication strategy through multisensory experiences. Other findings revealed that the presentation of visual messages that lead to the concept of sustainable tourism provides differentiating value and increases the attractiveness of destinations in the eyes of tourists. The implication of this study is the importance of utilizing experience-based interactive technology in tourism branding strategies, especially in increasing local wisdom and sustainability values as destination competitiveness in the digital era.